Sociodemographic Determinants of Financial Literacy Levels - Castañeda Francisco; Ormazábal Francisco; Cisternas Carla (Studies in Business and Economics, 2022)
This article analyses the sociodemographic determinants associated with the financial literacy levels of the Chilean population based on three dimensions: (1) knowledge; (2) behaviour; and (3) attitude. The study draws from data of the first and, thus far, the only national survey that has measured financial competency, conducted in 2016 by the Organisation for Economic Cooperation and Development (OECD), funded by the Financial Market Commission (CMF in Spanish) and the Andean Development Corporation (CAF in Spanish). It analyses the impact sociodemographic factors such as sex, age, education, and employment situation have on the financial literacy level of the population surveyed (N = 1.224). For each dimension, logistic regression models were adjusted consistent with the global financial literacy index. This method aimed to calculate, based on these variables, the probability that an individual may possess adequate knowledge, behaviour, and financial attitude. The findings indicate that a person between 30 and 60 years old, with a high education level, who earns a high income, will have a greater probability of possessing an adequate financial literacy level.